KONSEP PEMERINTAHAN DALAM ALQURAN: ANALISIS MAKNA KHALÄªFAH DALAM PERSPEKTIF FIQH POLITIK - Jumat, Abd. Gani (Hunafa: Jurnal Studia Islamika, 2014)
This article discusses the concept of governance in the Koran. Key terms that will be elaborated is the term Caliphate and derivation by using the approach of political fiqh. In the Koran, there are other terms that also connotes leadership, among others: imÄm, Å«lÄ« al-Amr, and al-Sulá¹Än. The use of these terms in accordance with their respective context. But the term is more often used by the caliphs of God for the meaning of power and authority. However, in essence, the Qur'an as the revelation of God's holy, does not contain or explain the system and political order of government or a particular form of state that must be used by Muslims, but it only contains the basic values of ethics and political morality to serve as a guide in the national and state .Kata Kunci : Alquran, khilafah, Â fiqh politik, pemerintahan.